Protective Effects of Cyphomandra betacea Extract Against Hydrogen Peroxide-induced Oxidative Stress in 3T3 Cells and Synergistic Anticancer Properties in HepG2 and MDA-MB-231 Cell Lines: Anticancer Properties of Cyphomandra betacea (Biological Sciences - PJSIR, 2024)
Using the MTT 3-(4, 5-dimethylthiazol-2yl-2, 5-diphenyltetrazolium bromide) assay induced by hydrogen peroxide (H2O2) and the ability to increase the cytotoxicity of doxorubicin in HepG2 and MDA-MB-231 cells, the protective effects of ethanolic extract of tamarillo were assessed in the current study. The cells were pre-treated with tamarillo ethanolic extract at 10 g/mL for 4 h before being exposed to 0.6 mM H2O2 for 3 h showed the greatest protection, with a significant increase (P 0.05) in cell viability of 79% compared to the control (57%). The results support a role that cyto-protective effect of tamarillo and doxorubicin which low in toxicity opens a new possible approach for possible future use in conventional chemotherapeutic drugs and radiation therapy.